A multifunctional film material with cellulose / graphene-Mxene hybrid interwoven structure and preparation method thereof

Through the multifunctional film material with cellulose/graphene-Mxene hybrid interwoven structure, the existing flexible thermal conductive film has solved the problem of low penetration and insufficient mechanical strength in thermal management applications, and achieved high mechanical strength and excellent flexibility and low-cost thermal conductivity, suitable for a variety of thermal management applications.

CN116515146BActive Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202310502993.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2024-12-13
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The existing flexible thermal conductive films exhibit low penetration in thermal management applications, and cannot effectively transfer heat from the heat source to the radiator vertically. Most materials have insufficient mechanical strength and flexibility, making it difficult to meet high mechanical strength and excellent The need for flexibility.

Method used

Using a multifunctional film material with a hybrid interwoven structure of cellulose/graphene-Mxene, the combination of MXene, dopamine hydrochloride and corn stalk powder forms nano-scale entanglements and hydrogen bonds, and using PVA as a binder, it is prepared with high quality. Composite materials with mechanical strength, excellent flexibility and low thickness.

Benefits of technology

It achieves high mechanical strength, excellent water stability and thermal stability, improves thermal conductivity and photothermal conversion efficiency, and maintains a stable structure at high temperatures, and has a wide range of raw materials, low cost, environmentally friendly and pollution-free, suitable for flexible radiators and wearable technology and other thermal management applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116515146B_ABST
    Figure CN116515146B_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional film material with a cellulose-graphene-MXene hybrid interwoven structure and a preparation method thereof. The preparation method comprises: step 1: surface functionalization of MXene nanosheets to grow a layer of polydopamine coating on the MXene nanosheets in a Tris buffer; step 2: extracting cellulose from corn stalk powder to obtain cellulose slurry; step 3: pouring functionalized MXene and graphene into the cellulose slurry together, stirring until the mixture is uniformly mixed, and then ball milling to obtain a mixed slurry; step 4: mixing the mixed slurry obtained in step 3 with PVA and heating, pouring the mixed solution into a mold and drying to obtain a multifunctional composite film; the material has a wide source of raw materials, a simple preparation process, low cost, and no pollution, and the prepared multifunctional composite material with a cellulose / graphene / MXene hybrid interwoven structure has excellent photothermal performance, high flexibility, good thermal conductivity and photothermal conversion performance, high wear resistance and recyclability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, relates to a thermally conductive film material and a preparation method thereof, and specifically relates to a multifunctional film material having a cellulose / graphene-Mxene hybrid interwoven structure and a preparation method thereof. Background Art

[0002] Due to the rapid development of high-power densification and high miniaturization of electronic devices, in the fields of communications, military and energy storage systems, electronic devices urgently need effective thermal management, and the main goal of thermal management is to transfer excess energy in electronic devices to the surrounding environment. Typical thermal conductive materials, including thermal grease, thermal adhesive, thermal pads and bulk polymer composites with high isotropic thermal conductivity, have been widely used as thermal interface materials (TIM) and heat sinks in the electronics field. However, compared with traditional thermal conductive materials, thermal conductive films with excellent flexibility and ultra-high planarity have received increasing attention, and significant efforts have been made in the development of flexible in-plane thermal conductive films, including pure polymer films, all-carbon films and polymer-based composite films.

[0003] Recently, extensive research efforts have been devoted to fabricating paper-like composites with hierarchical structures and ultrahigh in-plane k, such as reduced graphene oxide (RGO) films (1940 W (mK) -1 )、Carbon Nanotube (CNTs) Film (200W(mK) -1 )、boron nitride / polyvinyl alcohol (BN / PVA) film (120.7W(mK) -1 ), Boron nitride nanosheets / poly(diallyldimethylammonium chloride) (BNNS / PDDA) film (200W(mK) -1 ) and BNNS / nanofibrillar cellulose (NFC) film (145.7W(mK) -1 ).

[0004] Constructing an effective thermally conductive filler network and reducing phonon scattering at interfaces (filler / filler, polymer / polymer, and filler / polymer) are the main strategies to obtain thermally conductive polymer composite films. Even more impressively, a metal-like thermal conductivity of 63 W (mK) has been achieved. -1 Ultra-stretched ultra-high molecular weight polyethylene film, while the thermal conductivity of ordinary polymers is only about 0.2W (mK) -1 During polymerization or ultra-stretching processing, transforming the molecular chain structure of the polymer into a regular arrangement in a specific direction is the main strategy to obtain intrinsically thermally conductive polymer films. In summary, thermally conductive films with excellent flexibility and ultra-high thermal conductivity have been widely studied.

[0005] Unfortunately, most of these flexible thermally conductive films cannot be used in common thermal management applications such as TIM to effectively transfer heat vertically from the heat source to the heat sink because these films usually show very low through-plane. However, compared with isotropic thermal conductive materials, thermally conductive films with low thickness, high mechanical strength and excellent flexibility show great potential in thermal management applications such as flexible heat sinks, wearable technology, personal thermal management, skin electronics and energy storage devices. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a multifunctional thin film material with a cellulose / graphene-Mxene hybrid interwoven structure and a preparation method thereof. The prepared thermal conductive film has low thickness, high mechanical strength and excellent flexibility, and at the same time has high photothermal conversion efficiency and high wear resistance, recyclability, and a wide range of raw material sources, a simple preparation process, low cost, and is environmentally friendly and pollution-free.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure comprises the following steps:

[0009] Step 1: Add MXene and dopamine hydrochloride into a Tris buffer solution with a pH value of 8.5 according to the ratio of the mass of MXene nanosheets, the mass of dopamine hydrochloride and the volume of Tris buffer solution of 1 g:1 g:(50-75) mL, and stir continuously. After the mixture is centrifuged and washed, MXene@PDA is obtained.

[0010] Step 2: Weigh choline chloride and oxalic acid dihydrate in a mass ratio of (1-1.5) : 1, mix them, and then stir them thoroughly under heating conditions of 80-100°C to dissolve them until a transparent liquid is formed. Then add corn straw powder in a mass ratio of (100-150) mL to corn straw powder of (1.8 g). Continue stirring at the same temperature for 2-3 hours to form a mixed solution. Then mix the mixed solution with distilled water in a volume ratio of 1: (10-15) until it is uniform. After filtering and washing, the filter residue is dispersed in distilled water and acetic acid and sodium chlorite are added according to the mass ratio of the filter residue, the volume of distilled water, the volume of acetic acid and the mass ratio of sodium chlorite being 1g:(100-150)mL:(0.5-1.0)mL:(2-3)g, and then heated and stirred at 90-100°C for 5-6 hours, and then filtered and washed, and the solid matter is dispersed in water to prepare a cellulose slurry with a concentration of 20-30mg / mL;

[0011] Step 3: Mix the mass of MXene@PDA, the mass of graphene and the volume ratio of cellulose slurry at 1 g:2 g:(300-400) mL and perform ball milling to obtain a mixed slurry;

[0012] Step 4: Add polyvinyl alcohol to the mixed slurry obtained in step 3 according to the mass ratio of the mixed slurry volume to PVA of (100-150) mL: 1-2 g, and stir at 100°C for 2-3 hours. Pour the mixed liquid into a mold and dry it to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

[0013] The present invention also has the following technical features:

[0014] Preferably, the Tris buffer described in step 1 is prepared by adding 3.0285 g Tris and 0.6125 ml concentrated hydrochloric acid to 500 mL distilled water and stirring until the mixture is uniformly mixed.

[0015] Preferably, the continuous stirring time in step 1 is 20 to 24 hours.

[0016] Preferably, the rotation speed of the centrifugal separation in step 1 is 8000 rpm.

[0017] Preferably, the washing in step 1 and step 2 is washing with distilled water for 3 to 5 times.

[0018] Preferably, the sufficient stirring in step 2 is continuous stirring for 2 to 3 hours.

[0019] Preferably, the ball milling treatment time in step three is 12 to 16 hours.

[0020] Preferably, the drying in step 4 is performed at 40-50° C. for 12 hours.

[0021] The present invention also protects a multifunctional film material having a cellulose / graphene-Mxene hybrid interwoven structure prepared by the method as described above.

[0022] Compared with the prior art, the present invention has the following technical effects:

[0023] The preparation method of the present invention is very simple and does not require any extra impurity removal steps. The solvent used in the entire preparation process is color-protecting, environmentally friendly and pollution-free. It only requires simply etching MXene, dissolving corn straw powder to extract cellulose, mixing graphene, MXene@PDA and cellulose solution, and then ball milling to form a hybrid self-interwoven structure of the two-dimensional material in the cellulose micro-nano fibril network. Then, PVA is used as a binder to give the NC / G-MXene@PDA / PVA composite material excellent mechanical properties.

[0024] The multifunctional film material prepared by the present invention shows high mechanical strength, excellent water stability and thermal stability; nano-scale entanglement and hydrogen bonds are formed between graphene, Mxene and cellulose micro-nano fibrils, and the entangled micro / nano cellulose itself plays the role of a reinforcing phase, and then interacts with the micro / nano cellulose through hydrogen bonds and van der Waals forces to form a strong hybrid interwoven structure, and the composite PVA has a denser structure, giving the multifunctional material excellent mechanical properties. Due to the dense structure of the multifunctional material, it is difficult for water molecules to penetrate into the material, so it has good stability in water; the tensile strength of the multifunctional film is as high as 300Mpa or more, and the composite film still maintains structural stability under high temperature conditions. After the thermal conductivity test of the wood cellulose friction material, it is found that it has excellent thermal conductivity and light-heat conversion performance, and the material has low thickness and excellent flexibility;

[0025] The raw material used in the present invention is corn stalk powder, which is an agricultural waste material. As a typical green natural biomass material, it has the advantages of wide sources, large reserves, green and environmental protection, and low price.

[0026] The synthesis process of the present invention is simple and does not require overly complicated synthesis steps. It shows great potential in thermal management applications such as flexible heat sinks, wearable technology, personal thermal management, skin electronics and energy storage devices.

[0027] The material prepared by the present invention can not only be recycled using laboratory methods, but also can be degraded by microorganisms in the natural environment due to its material composition with cellulose and degradable PVA as the main skeleton, thus having a lower impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a SEM microstructure image of MXene@PDA prepared in the present invention;

[0029] Figure 2 is a SEM microstructure image of the hybrid interwoven framework of the NC / G-MXene@PDA / PVA composite material prepared in the present invention;

[0030] Figure 3 is a cross-sectional SEM microstructure diagram of the NC / G-MXene@PDA / PVA composite material prepared by the present invention;

[0031] Figure 4 is a macroscopic photograph of the NC / G-MXene@PDA / PVA composite material prepared by the present invention;

[0032] Figure 5It is a photothermal performance conversion efficiency diagram of the NC / G-MXene@PDA / PVA composite material prepared by the present invention;

[0033] Figure 6 This is a test diagram of thermal conductivity of the NC / G-MXene@PDA / PVA composite material prepared by the present invention;

[0034] Figure 7 is a stress-strain curve diagram of the NC / G-MXene@PDA / PVA composite material prepared by the present invention;

[0035] Figure 8 This is a test chart of the wear resistance of the NC / G-MXene@PDA / PVA composite material prepared by the present invention. DETAILED DESCRIPTION

[0036] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0037] In the following examples, the preparation method of Tris buffer with p h of 8.5 is to add 3.0285 g Tris and 0.6125 ml concentrated hydrochloric acid with a mass concentration of 36.46% into 500 mL distilled water and stir until the mixture is uniform.

[0038] Example 1

[0039] A method for preparing a multifunctional material having a cellulose / graphene-Mxene hybrid interwoven structure comprises the following steps:

[0040] Step 1: 1 g MXene and 1 g dopamine hydrochloride were added to 75 mL Tris buffer with a pH of 8.5 and stirred for 24 hours. After that, the mixture was centrifuged at 8000 rpm and washed with distilled water for 5 times to obtain MXene@PDA.

[0041] Step 2: Weigh 12g of choline chloride and 12g of oxalic acid dihydrate, mix them, and then continue to stir for 3 hours under heating conditions at 80°C to dissolve them. After forming a transparent liquid, add 1.8g of corn straw powder per 100ml, stir for 3 hours at the same temperature, then add distilled water at a volume ratio of 1:15, mix until uniform, filter and wash with distilled water 5 times, disperse 1g of the filter residue in 100mL of distilled water, add 1.0mL of acetic acid and 3g of sodium chlorite, heat and stir at 90°C for 6 hours for bleaching, and finally filter and wash with water 5 times, and then disperse the solid matter in water to prepare a cellulose slurry with a concentration of 20mg / mL;

[0042] Step 3: Weigh 0.5 g of Mxene and 1 g of graphene, mix them, pour them into 200 mL of the cellulose slurry with the concentration obtained in step 2, and ball-mill for 16 hours to obtain a mixed slurry;

[0043] Step 4: Add 4 g of PVA to the mixed slurry obtained in step 3 and stir at 100 °C for 3 hours. Pour the mixed liquid into a mold and dry it at 50 °C for 12 hours to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

[0044] Figure 1 is the SEM image of MXene@PDA prepared in Example 1. Figure 1 It can be clearly observed that the in situ synthesized polydopamine adheres to the surface of MXene to form a protective layer, which can effectively prevent the oxidation of MXene nanosheets.

[0045] Figure 2 is the SEM image of the NC / G-MXene@PDA framework structure prepared in Example 1. Figure 2 It can be found that MXene, graphene and cellulose together form a lamellar hybrid interwoven structure, which greatly reduces the performance loss caused by uneven distribution of fillers and enhances the mechanical properties and durability of the composite material.

[0046] Figure 3 is a cross-sectional SEM image of the NC / G-MXene@PDA / PVA composite material prepared in Example 1. Figure 3 It can be found that the layer structure forms a tightly packed structure after densification, and PVA as an adhesive further enhances the bonding strength between layers, giving the composite material excellent mechanical properties.

[0047] Figure 4 is a macroscopic photograph of the NC / G-MXene@PDA / PVA composite material prepared in Example 1. Figure 4 As shown, it can be curled arbitrarily and has excellent flexibility.

[0048] Figure 7 is a stress-strain curve of the NC / G-MXene@PDA / PVA composite material prepared in Example 1, as shown in Figure 7 As shown, compared with the pure material without the G-MXene@PDA hybrid interwoven structure, its tensile strength is increased by 313.3%, showing excellent mechanical strength.

[0049] Figure 8 The wear resistance test diagram of the NC / G-MXene@PDA / PVA composite material prepared in Example 1 is shown in FIG. Figure 8As shown in the figure, under high load (10N) conditions, it has a long-lasting stable friction coefficient and low wear rate.

[0050] Example 2

[0051] A method for preparing a multifunctional material having a cellulose / graphene-Mxene hybrid interwoven structure comprises the following steps:

[0052] Step 1: 1 g MXene and 1 g dopamine hydrochloride were added to 50 mL Tris buffer with a pH of 8.5 and stirred for 20 hours. After that, the mixture was centrifuged at 8000 rpm and washed with distilled water for 3 times to obtain MXene@PDA.

[0053] Step 2: Weigh 15g of choline chloride and 10g of oxalic acid dihydrate, mix them, and then continue to stir for 2 hours under heating conditions at 100°C to dissolve them. After forming a transparent liquid, add 1.8g of corn straw powder per 150ml, stir for 2 hours at the same temperature, then add distilled water at a volume ratio of 1:10, mix until uniform, filter and wash with distilled water 4 times, disperse 1g of the filter residue in 150mL of distilled water, add 0.5mL of acetic acid and 2g of sodium chlorite, heat and stir at 100°C for 5 hours for bleaching, and finally filter and wash 4 times, then disperse the solid matter in water to prepare a cellulose slurry with a concentration of 30mg / mL;

[0054] Step 3: Weigh 1 g of Mxene and 2 g of graphene, mix them, pour them into 300 mL of the cellulose slurry with the concentration obtained in step 2, and ball-mill for 12 hours to obtain a mixed slurry;

[0055] Step 4: Add 2 g of PVA to the mixed slurry obtained in step 3 and stir at 100 °C for 2 hours. Pour the mixed liquid into a mold and dry it at 40 °C for 12 hours to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

[0056] Figure 5 The photothermal conversion performance of the NC / G-MXene@PDA / PVA composite material prepared in Example 2 is shown in FIG. Figure 5 As shown, the photothermal conversion efficiency is increased by 130% compared with the pure material without the G-MXene@PDA hybrid interwoven structure.

[0057] Figure 6 The thermal conductivity and heat dissipation performance of the NC / G-MXene@PDA / PVA composite material prepared in Example 2 is as follows: Figure 6 As shown, compared with the pure material without the G-MXene@PDA hybrid interwoven structure, its thermal conductivity efficiency when placed on the surface of the heating platform is significantly improved.

[0058] Example 3

[0059] A method for preparing a multifunctional material having a cellulose / graphene-Mxene hybrid interwoven structure comprises the following steps:

[0060] Step 1: 1 g MXene and 1 g dopamine hydrochloride were added to 60 mL Tris buffer with a pH of 8.5 and stirred for 22 hours. After that, the mixture was centrifuged at 8000 rpm and washed with distilled water for 4 times to obtain MXene@PDA.

[0061] Step 2: Weigh 15g of choline chloride and 13g of oxalic acid dihydrate, mix them, and then continue to stir for 2.5 hours at 90°C to dissolve them. After forming a transparent liquid, add 1.8g of corn straw powder per 120ml, stir for 2.5 hours at the same temperature, then add distilled water at a volume ratio of 1:12, mix until uniform, filter and wash with distilled water 5 times, disperse 1g of the filter residue in 120mL of distilled water, add 0.8mL of acetic acid and 2.5g of sodium chlorite, heat and stir at 95°C for 5.5 hours for bleaching, filter and wash 3 times, and then disperse the solid matter in water to prepare a cellulose slurry with a concentration of 25mg / mL;

[0062] Step 3: Weigh 1 g of Mxene and 2 g of graphene, mix them, pour them into 350 mL of the cellulose slurry with the concentration obtained in step 2, and ball-mill for 14 hours to obtain a mixed slurry;

[0063] Step 4: Add 4 g of PVA to the mixed slurry obtained in step 3 and stir at 100 °C for 2.5 hours. Pour the mixed liquid into a mold and dry it at 45 °C for 12 hours to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

[0064] Example 4

[0065] A method for preparing a multifunctional material having a cellulose / graphene-Mxene hybrid interwoven structure comprises the following steps:

[0066] Step 1: Add 2 g MXene and 2 g dopamine hydrochloride into 150 mL Tris buffer with a pH of 8.5 and stir for 24 hours. Centrifuge at 8000 rpm and wash with distilled water for 5 times to obtain MXene@PDA.

[0067] Step 2: Weigh 12g of choline chloride and 12g of oxalic acid dihydrate, mix them, and then continue to stir for 3h under heating conditions at 80°C to dissolve them. After forming a transparent liquid, add 1.8g of corn straw powder per 150ml, stir for 3 hours at the same temperature, then add distilled water at a volume ratio of 1:13, mix until uniform, filter and wash with distilled water 5 times, disperse 1g of the filter residue in 150mL of distilled water, add 1.0mL of acetic acid and 2g of sodium chlorite, heat and stir at 90°C for 6 hours for bleaching, and finally filter and wash with water 5 times, and then disperse the solid matter in water to prepare a cellulose slurry with a concentration of 30mg / mL;

[0068] Step 3: Weigh 1 g of Mxene and 2 g of graphene, mix them, pour them into 400 mL of the cellulose slurry with the concentration obtained in step 2, and ball-mill for 16 hours to obtain a mixed slurry;

[0069] Step 4: Add 4 g of PVA to the mixed slurry obtained in step 3 and stir at 100 °C for 3 hours. Pour the mixed liquid into a mold and dry it at 50 °C for 12 hours to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solution described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solution to deviate from the scope of the technical solution of the present invention.

Claims

1. A method for preparing a multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure, It is characterized in that The following steps are involved: Step 1: Add MXene and dopamine hydrochloride into a Tris buffer solution with a pH value of 8.5 according to the ratio of the mass of MXene nanosheets, the mass of dopamine hydrochloride and the volume of Tris buffer solution of 1 g:1 g:(50-75) mL, and stir continuously. After the mixture is centrifuged and washed, MXene@PDA is obtained. Step 2: Weigh choline chloride and oxalic acid dihydrate in a mass ratio of (1-1.5) : 1, mix them, and then stir them thoroughly under heating conditions of 80-100°C to dissolve them until a transparent liquid is formed. Then add corn straw powder in a mass ratio of (100-150) mL to corn straw powder of (1.8 g). Continue stirring at the same temperature for 2-3 hours to form a mixed solution. Then mix the mixed solution with distilled water in a volume ratio of 1: (10-15) until it is uniform. After filtering and washing, the filter residue is dispersed in distilled water and acetic acid and sodium chlorite are added according to the mass ratio of the filter residue, the volume of distilled water, the volume of acetic acid and the mass ratio of sodium chlorite being 1g:(100-150)mL:(0.5-1.0)mL:(2-3)g, and then heated and stirred at 90-100°C for 5-6 hours, and then filtered and washed, and the solid matter is dispersed in water to prepare a cellulose slurry with a concentration of 20-30mg / mL; Step 3: Mix the mass of MXene@PDA, the mass of graphene and the volume ratio of cellulose slurry at 1 g:2 g:(300-400) mL and perform ball milling to obtain a mixed slurry; Step 4: Add polyvinyl alcohol to the mixed slurry obtained in step 3 according to the mass ratio of the mixed slurry volume to PVA of (100-150) mL: 1-2 g, and stir at 100°C for 2-3 hours. Pour the mixed liquid into a mold and dry it to obtain a multifunctional NC / G-MXene@PDA / PVA composite material with a hybrid interwoven structure.

2. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The Tris buffer described in step 1 is prepared by adding 3.0285 g Tris and 0.6125 ml concentrated hydrochloric acid to 500 mL distilled water and stirring until the mixture is uniform.

3. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The continuous stirring time described in step 1 is 20 to 24 hours.

4. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The rotation speed of the centrifugal separation described in step 1 is 8000 rpm.

5. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The washing described in step 1 and step 2 is washing with distilled water for 3 to 5 times.

6. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The sufficient stirring described in step 2 is continuous stirring for 2 to 3 hours.

7. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The ball milling time described in step 3 is 12 to 16 hours.

8. The method for preparing the multifunctional thin film material having a cellulose / graphene-Mxene hybrid interwoven structure according to claim 1, It is characterized in that The drying described in step 4 is drying at 40-50° C. for 12 hours.

9. A multifunctional film material having a cellulose / graphene-Mxene hybrid interwoven structure prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method of production of nanoporous membranes for water purification from metal IONS at low differential pressures

    CA2963431A1

  • Method for preparing micro / nanofiber graphene composite membrane from recycled corrugated paper

    CN103387686A

  • Preparation method of tough graphene / cellulose composite heat-conductive and electro-conductive film

    CN107293377A

  • MXene-base composite fiber super capacitor

    CN107680824A

  • Preparation method of telescopic MXene / graphene composite aerogel with high electromagnetic shielding effect

    CN108620003A